About cookies on this site Our websites require some cookies to function properly (required). In addition, other cookies may be used with your consent to analyze site usage, improve the user experience and for advertising. For more information, please review your options. By visiting our website, you agree to our processing of information as described in IBM’sprivacy statement. To provide a smooth navigation, your cookie preferences will be shared across the IBM web domains listed here.
February 2005
Answer:
Let r[k] denote the length of the hypotenuse of triangle Tk, so that r[k-1] is the length of one leg of Tk, and r[0]=1 for starters. We have r[k-1]/r[k]=cos((/2)/2^k). This recurrence relation, along with initial condition r[0]=1, is solved by r[k]=(2^k)sin((
/2)/2^k). (Apply the formula for sin(2b)=2sin(b)cos(b) to b=((
/2)/2^k).) Restate this as r[k]=(
/2)(sin(c[k])/c[k]) where c[k]=(
/2)/2^k, notice that c[k] tends to 0 as k increases, and use limit(sin(z)/z)=1 as z tends to 0, to deduce that r[k] tends to the limit p/2, which answers Part 1.
Notice that in the above expression, c[k] is also the angle between the x-axis and the hypotenuse of triangle Tk. So the point with polar coordinates (r,)=(r[k],c[k]) is one of the vertices of triangle Tk. A curve passing through all such vertices is given by r=(
/2)(sin(
)/
). This answers Part 2.
Converting this to rectangular coordinates, we find y/x = tan [ y / 2(x^2+y^2) ] , to answer Part 3.
If you have any problems you think we might enjoy, please send them in. All replies should be sent to: ponder@il.ibm.com